Two-echelon reverse supply chain in collecting waste electrical and electronic equipment: A game theory model. (December 2018) - Guo, Lingling; Qu, Ying; Tseng, Ming-Lang; Wu, Chunyou; Wang, Xiuyan
Highlights: A two-echelon reverse supply chain is developed using a game model. Coordinated collection strategies considering publicity are investigated. Case studies of changes in recovery price, quantity, and publicity efforts are discussed. Optimal recycling channel choice for recyclers and processors is examined. Abstract: This study contributes to the literature by proposing coordination strategies between recyclers and processors in the collection of waste electrical and electronic equipment. Due to the increase in e-waste and its serious environmental consequences, much attention has been paid to recycling and remanufacturing. This study proposes a two-echelon reverse supply chain and deals with the differential game model by introducing recycling publicity. Illustrative examples are used to examine the differences and changes in recovery price, quantity, and publicity effort among three case studies. The results indicate that, when a processor undertakes publicity costs, the recovery quantity can be increased by improving recovery publicity efforts, rather than raising the recovery price, but when publicity expenses are paid by the recycler, the recovery quantity may be enhanced by bringing up the unit direct recovery price while the degree of recovery publicity efforts is minimal. A centralized decision is made, and recovery price, recovery quantity, and publicity efforts are maximized. These results can help achieve an optimal approach to the recycling of waste electrical and electronic equipment in a reverse supply chain.